Socio-Demographic and Housing Condition Urban Slum and Rural Households, Gujarat, India - Bipin Prajapati; Kanita Banker; Jignesh Chauhan; Sunil Nayak (Medsci Publications, 2017)
Background: By 2025-26 the number of middle class households in India is likely to more than double from the 2015-16 levels to 113.8 million households or 547 million individuals. Objectives: To study the difference between urban slum and rural area regarding social, demographic and housing condition. Materials and Methods: This cross-sectional secondary data analysis study was conducted at RHTC - Hadiyol and UHTC - Himmatnagar of GMERS medical college, Himmatnagar, Sabar- kantha district, Gujarat during 1st January 2016 to 30th August 2016. Study included 500 household from RHTC with 2250 members of rural area and 500 households from UHTC with 2418 members of urban slum area by purposive sampling method. Results: Almost 93.8% rural & 86.4% urban slum population was residing their own house and 66.2% rural & 53.2% urban slum population have "pucca" house. Mean family size was 4.5 ± 1.5 in rural and 4.8 ± 1.7 in urban slum households. Separate kitchen was present in 54.4% rural & 30.4% urban slum houses. Conclusion: Study reveal the socio-demographic and housing status difference between urban slum & rural area regarding own house, number of family members, kitchen, latrine, bathroom, overcrowding, sanitary practices.